2019
DOI: 10.1101/817023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meningeal lymphatic dysfunction exacerbates traumatic brain injury pathogenesis

Abstract: Traumatic brain injury (TBI) has emerged as a leading cause of death and disability. Despite being a growing medical issue, the biological factors that promote central nervous system (CNS) pathology and neurological dysfunction following TBI remain poorly characterized. Recently, the meningeal lymphatic system was identified as a critical mediator of drainage from the CNS. In comparison to other peripheral organs, our understanding of how defects in lymphatic drainage from the CNS contribute to disease is limi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 64 publications
2
76
0
Order By: Relevance
“…When meningeal lymphatics are ligated in mice, it worsens the disease phenotype as a result of meningeal lymphatic dysfunction (Zou et al, 2019). Likewise, meningeal lymphatic disruption is accompanied by worsened outcomes in different models of experimental stroke (Chen et al, 2019;Yanev et al, 2020), and in a brain concussion model, where they seem to regulate the extent of edema, the degree of microglial activation, and overall neuronal degeneration (Bolte et al, 2019). Together, these findings suggest that meningeal lymphatics may be a viable therapeutic target for neurological disorders associated with protein accumulation/aggregation.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…When meningeal lymphatics are ligated in mice, it worsens the disease phenotype as a result of meningeal lymphatic dysfunction (Zou et al, 2019). Likewise, meningeal lymphatic disruption is accompanied by worsened outcomes in different models of experimental stroke (Chen et al, 2019;Yanev et al, 2020), and in a brain concussion model, where they seem to regulate the extent of edema, the degree of microglial activation, and overall neuronal degeneration (Bolte et al, 2019). Together, these findings suggest that meningeal lymphatics may be a viable therapeutic target for neurological disorders associated with protein accumulation/aggregation.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…On the other hand, the mammalian TBI model is more advanced in its robust research background focusing on the mechanism and important biomarkers. 117,[163][164][165][166][167][168] In addition to that, non-mammalian research has not conducted any research on inducing stem cell for brain injury as been conducted previously in this study with mammalian model. 169,170 Indeed, one of the study showed successful xenotransplantation of human iPSC-derived NSCs and isogenic neural cell progenies in a mouse model.…”
Section: Future Direction Of Non-mammalian Animal Model In Traumatimentioning
confidence: 98%
“…264,265 For instance, TBI has recently been shown to compromise meningeal lymphatic function, namely its ability to drain inflammatory byproducts to lymph nodes following injury. 266 Interestingly, meningeal lymphatic drainage defects are known to significantly increase meningeal Aβ load and to provoke memory deficits in 5xFAD AD mice. 265 Therefore, meningeal lymphatic dysfunction may provide another explanation for the association between AD pathogenesis and brain injury, with promising clinical implications that require further investigation.…”
Section: Role Of Age Environmental Factors and Sex In Admentioning
confidence: 99%